Workplace with better Health, Safety, and Environment for Organizational Well-being - Rabindranath Jana (International Journal of Pollution: Prevention & Control, 2024)
In the realm of workplaces, prioritizing the welfare of employees and upholding environmental protection has gained utmost significance. There are multifaceted approaches to achieving a harmonious balance between workplace health, safety, and environmental sustainability. For the better Health, Safety and Environment, the integration of comprehensive policies, cutting-edge technologies, and a culture of continuous improvement to foster a secure, healthy, and environment are essential. The evolutions of workplace health and safety standards, emphasizing the paradigm shift from compliance-driven approaches to proactive strategies are nowadays well accepted. By examining case studies and industry best practices, it is realized to underscores the importance of cultivating a safety-centric culture where employees are not merely recipients of guidelines but active participants in creating a secure workplace. Establishing a workplace with a robust Health, Safety, and Environment (HSE) focus necessitates a comprehensive strategy encompassing leadership dedication, active involvement of employees, continual training, and a steadfast dedication to ongoing enhancements. In today's dynamic work environment, embracing the nexus between employee well- being, safety, and environmental sustainability is not merely a choice but a strategic imperative. By aligning policies, technologies, and organizational culture towards these objectives, workplaces can transcend conventional norms and emerge as beacons of excellence. Through concerted efforts, organizations can not only fulfill their duty of care towards employees but also play a pivotal role in advancing broader societal goals of sustainability and responsible stewardship of resources. So the convergence of workplace health, safety, and environmental sustainability underscores the need for proactive and comprehensive strategies. By prioritizing employee welfare, fostering a safety-centric culture, and embracing continuous improvement, workplaces can transcend mediocrity and emerge as exemplars of excellence in the modern era.
Keywords: Environment; Health; Safety; Workplace; well-being